Performance of ImproGene cfDNA blood collection tubes for mutation analysis in cancer patients. (1st September 2022) - Zhang, Shu; Zhou, Dongyao; Li, Siyun; Bai, Yingming; Huang, Bo; Han, Jianhong; Xu, Mingfei; Wang, Sina; Deng, Guanhua
Abstract: With the widely application of liquid biopsy and the development of detection technology, the standardization of pre-analysis procedures is necessary. For controlling pre-analysis variation of circulating tumor DNA (ctDNA) in blood samples, the blood collection tubes for ctDNA preservation particularly contribute a lot. The objective of this study was to investigate whether ImproGene® Cell Free DNA Tube (ImproGene tube) can be used in sample collection, preservation and NGS based mutation detection for ctDNA. We investigated hemolysis and cell free DNA (cfDNA) concentration of blood samples stored in ImproGene tubes and detected β-actin, LINE1 and exogenous gene level by qPCR. We compared cfDNA and RNA quantity between samples in ImproGene tube and Streck Cell-Free DNA BCT® (Streck tube). And 10 gene mutations and three fusion mutations analysis were compared by sequencing. When stored at room temperature within 7 days in ImproGene tubes, blood samples had no visible hemolysis and the cfDNA concentration, levels of β-actin, LINE1 and exogenous gene remained stable which means no genomic DNA release and cfDNA was protected. There was no significant difference in cfDNA and RNA quantity between ImproGene tubes and Streck tubes. Furthermore, based on this limited data set, ImproGene tubes showed increased detection rates of low-level mutations. Therefore, ImproGene Cell Free DNA Tubes may have promising applications in sample collection, preservation and NGS based mutation detection for ctDNA by its good preservation performance.